AHMED ABDA’S CLAIM ABOUT THE EXISTENCE OF SOME PROPHETIC HADITHS IN AL-BUKHARI’S BOOK CONTRADICTING WITH THE GLORIOUS QUR’AN: A CRITICAL STUDY - MOHAMMED , KHALID (Islamic Sciences Journal, 2023)
This research deals with an important issue in the foundations of our religion, belief and our sanctities. This religion was exposed, from the time of the Companions - may Allah be pleased with them - and after the death of the Prophet - peace be upon him - to a variety of attempts to undermine it and to question and challenge the most important pillars (Sunnah) depending on allegorical texts. Nowadays, though they are considered Muslims in their belief, we have some of those who challenge Al-Bukhari and Muslim’s books. This research some of these allegorical texts that Ahmed Abda Maher used claiming that the two books ( Al-Bukhari and Muslim) include some prophetic hadiths that contradict with the Glorious Qur’an. These claims were critically and scientifically discussed and refuted.